The The Influence Of Early Children's Dental Health Monitoring Books On Parents' Knowledge In Az-Zahra Islamic Kindergarten, Jambi City - Febrianti, Sri; Muliadi, Muliadi; Suhartono, Suhartono (Riset Informasi Kesehatan, 2023)
Background: The results of the 2018 Basic Health Research (Riskesdas) show that the prevalence of caries in the 3-4 year age group is 81.5% and the caries prevalence in the 5-9 year age group is 92.6%. The average def-t for the age group 3-4 years was 6.2 and the average def-t for the 5-year age group was 8.1. Research conducted on all kindergarten students in Malalayang District showed that the prevalence of primary tooth caries was 90% with an average index def-t = 6.99.Method: The design in this study used a pre-experimental one group pre-test posttest. There were 30 samples in the study that met the inclusion and exclusion criteria. Results: The statistical test output shows that the p-value of knowledge is 0.000. Because the value 0.000 < 0.05, the hypothesis is accepted, which means there is a difference between the dental health knowledge scores for the pre-test and post-test.Conclusion: Monitoring books can increase parents' knowledge in Az-Zahra Islamic Kindergarten, Jambi City